Indwelling urethral versus suprapubic catheters in nursing home residents: determining the safest option for long-term use. Issue 2 (June 2019) - Gibson, K.E.; Neill, S.; Tuma, E.; Meddings, J.; Mody, L.
Summary: Background: The incidence of infectious complications has not been previously compared for two types of common urinary catheters used in the long-term care setting: indwelling urethral catheters and suprapubic catheters. Aim: To compare catheter-associated urinary tract infection (CAUTI) rates and multidrug-resistant organism (MDRO) colonization between nursing home residents with indwelling urethral and suprapubic catheters. Methods: Participants included 418 nursing home residents with an indwelling device enrolled in a previously published prospective targeted infection prevention study conducted between 2010 and 2013. Resident age, gender, function, comorbidities, and information on infections, antibiotic use, and recent hospitalizations were obtained at study enrolment, day 14, and every 30 days thereafter for up to one year. Microbiological samples were obtained from several anatomic sites at each visit. Cox proportional hazard models were adjusted for facility-level clustering and other covariates. Findings: In all, 208 study participants had an indwelling urinary catheter, contributing 21, 700 device-days; 173 (83%) with a urethral catheter, 35 (17%) with a suprapubic catheter. After covariate adjustment, the suprapubic group had a lower incidence of CAUTI (6.6 vs 8.8 per 1000 device-days; P = 0.05), were half as likely to be hospitalized (hazard ratio (HR) = 0.46; P < 0.01) and were 23% less likely to have had antibiotics in the past 30 days (HR = 0.77; P = 0.02). Among residents catheterized ≥90 days, the mean number of MDROs isolated in the suprapubic group was significantly higher than in the urethral group (0.57 vs 0.44; P = 0.01). Ciprofloxacin-resistant Gram-negative bacilli were frequent in both groups. Conclusion: Residents with a suprapubic catheter may have fewer CAUTIs, less hospitalization and less antibiotic use, but are more likely colonized with MDROs.